EFEKTIVITAS PENGELOLAAN HASIL WAKAF DALAM BENTUK WASIAT POLIS ASURANSI Studi Di Kspps Mawar Jatim Kecamatan Karanggeneng Kabupaten Lamongan 2022/2023 - Ahmadani Muhammad Khallaf; Masrokhin Masrokhin (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
In this study the topic discussed is the importance of the effectiveness of managing waqf proceeds in the form of an insurance policy will. In society, waqf is a very popular form of charity to help people in need. However, there are still many waqf that are not managed properly and do not provide maximum benefits for beneficiaries. Implementation of waqf will insurance policies can help overcome this problem by ensuring that waqf is managed properly and provides maximum benefits for beneficiaries. This study was conducted at KSPPS MAWAR East Java, Karanggeneng District, Lamongan Regency in 2022/2023 to obtain an overview of the effectiveness of yield management and its implementation. The results of this study are that in the Management of Cash Waqf at KSPPS MAWAR, Nazhir decided that with the existence of waqf in the form of an insurance policy will that had been carried out to develop waqf in this implementation in line with the benefits that must be implemented. Nazhir's considerations, with the MUI Fatwa both have the value of enforcing the benefit and benefits for the institution and the heirs that have been determined. So, the concept of maslahah from the MUI Fatwa in the issue of waqf management in the form of an insurance policy will has actually been upheld by Nazhir who manages KSPPS MAWAR.